2019
DOI: 10.1016/j.bja.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative systemic inflammation and perioperative myocardial injury: prospective observational multicentre cohort study of patients undergoing non-cardiac surgery

Abstract: Background: Systemic inflammation is pivotal in the pathogenesis of cardiovascular disease. As inflammation can directly cause cardiomyocyte injury, we hypothesised that established systemic inflammation, as reflected by elevated preoperative neutrophil-lymphocyte ratio (NLR) >4, predisposes patients to perioperative myocardial injury. Methods: We prospectively recruited 1652 patients aged !45 yr who underwent non-cardiac surgery in two UK centres. Serum high sensitivity troponin T (hsTnT) concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 48 publications
2
68
1
5
Order By: Relevance
“…Leucocyte data were obtained from the VISIONUK study (MREC:10/WNo03/25) [19]. Peripheral blood mononuclear cells (PBMCs) were isolated using Ficoll Hypaque (Amersham Biosciences, Little Chalfont, UK).…”
Section: Blood Sample Collection Isolation and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Leucocyte data were obtained from the VISIONUK study (MREC:10/WNo03/25) [19]. Peripheral blood mononuclear cells (PBMCs) were isolated using Ficoll Hypaque (Amersham Biosciences, Little Chalfont, UK).…”
Section: Blood Sample Collection Isolation and Cell Culturementioning
confidence: 99%
“…All samples were obtained in accordance with the North East York Research Ethics Committee 16/NE/0073. Leucocyte data were obtained from the VISIONUK study (MREC:10/WNo03/25) [19]. Leucocyte subsets were measured using a Sysmex XE2100 analyser (Sysmex, Milton Keynes, UK).…”
Section: Blood Sample Collection Isolation and Cell Culturementioning
confidence: 99%
“…Non‐cardiac surgery represents a potential cardiovascular risk factor, which could be related to elevated systemic inflammation (Ackland et al, ). In particular, this might be particularly important in patients that are considered at a high‐risk (Kristensen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of systemic inflammation have been associated with a significant and independent higher risk of incident cardiovascular disease (Pearson et al, ). Therapeutic interventions are capable of determining a short‐lived acute inflammatory response, which may trigger cardiovascular events as shown by the higher risk of myocardial infarction observed after non‐cardiac surgery (Ackland et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, overwhelming neutrophil immune responses serve a central role in the development of inflammatory injury. Recent research showed that inflammatory injuries mediated by overwhelming neutrophilic immune reactions are essential in the progression of several diseases such as sepsis, ischemia/reperfusion injury, myocardial injury, and acute lung injury 3‐5 . Excessive production of toxic reactive oxygen species (ROS) from activated neutrophils directly destroys lung tissue and indirectly induces interstitial edema due to poorer oxygenation in acute lung injury 6,7 .…”
Section: Introductionmentioning
confidence: 99%